Lipoedema and Pain: What is the role of the psyche? – Results of a pilot study with 150 patients with Lipoedema - Erbacher, Gabriele; Bertsch, Tobias (Phlebologie, 2020)
Introduction The present exploratory study is the first so far to investigate the psychological stress in the period before the development of pain symptoms typical for lipoedema.Methods 150 patients diagnosed with lipoedema syndrome were questioned in semi-structured interviews about psychological stress and were diagnosed with psychological disorders according to ICD-10 criteria. The development of the symptoms typical for lipoedema was recorded in a second interview. Both interviews were blended together in collaboration with the patients, this means Lipoedema-associated pain and psychological stress were related to time.Result Exactly 80 % of the patients diagnosed with lipedema show a high level of psychological distress immediately before the onset of lipedema-associated symptoms! In this study, mental distress was defined as the presence of a manifest mental disorder (ICD 10 F diagnosis) such as Depression, eating disorder or post-traumatic stress disorder and/or serious psychological distress such as burnout syndrome or chronic stress.Summary These results contradict a widespread statement that all psychological problems of patients with the diagnosis lipoedema syndrome are caused solely by lipoedema, that lipoedema even causes the patient’s mental disorder.Moreover, depression and posttraumatic stress disorders are significantly related to the maximum pain intensity estimated by patients in everyday life. This demonstrates that it is imperative to rethink lipoedema therapy and to implement a psychosocial pillar in an overall therapy concept.
Keywords: lipoedema; mental stress; mental disease; pain; scientific evidence; Lipödem; psychische Belastung; psychische Erkrankung; Schmerz; wissenschaftliche Evidenz